In vitro and in silico studies of silver nanoparticles (AgNPs) from Allium sativum against diabetes - D. Jini; S. Sharmila; A. Anitha; Mahalakshmi Pandian; R. M. H. Rajapaksha (Scientific Reports, 2022)
Abstract In the present study, the silver nanoparticles (AgNPs) were synthesized from the bulbs of Allium sativum, characterized by UV–visible spectroscopy, FT-IR, SEM, HR-TEM, EDAX analysis and investigated its action on the inhibition of starch digestion. The results proved that the biosynthesized nanoparticles were uniformly dispersed, spherical shaped with the size ranging from 10 to 30 nm. The phytochemical and FT-IR analysis showed the presence of phenols, terpenoids, and amino acids in the synthesized AgNPs. The cytotoxicity analysis revealed that the synthesized AgNPs were non-toxic to the normal cells. The synthesized AgNPs exhibited significant free radical scavenging activity. The in vitro antidiabetic activity showed that the synthesized AgNPs increased glucose utilization, decreased hepatic glucose production, inhibited the activity of starch digestive enzymes such as α-amylase and α-glucosidase, and were not involved in the stimulation of pancreatic cells for the secretion of insulin. The in silico antidiabetic activity analysis (molecular docking) also revealed that the silver atoms of the AgNPs interacted with the amino acid residues of α-amylase, α-glucosidase, and insulin. The present study proved that the AgNPs synthesized from A. sativum have prominent antidiabetic activity in terms of reducing the hyperglycemia through the increased glucose utilization, decreased hepatic glucose production, and the inhibition of α-amylase and α-glucosidase enzymes. So it can be used as a promising nanomedicine for the treatment of diabetes.